2011
DOI: 10.1523/jneurosci.3314-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Precerebellar Neurons Share Similar Intrinsic Excitability

Abstract: The cerebellum dedicates a majority of the brain’s neurons to processing a wide range of sensory, motor, and cognitive signals. Stereotyped circuitry within the cerebellar cortex suggests that similar computations are performed throughout the cerebellum, but little is known about whether diverse precerebellar neurons are specialized for the nature of the information they convey. In vivo recordings indicate that firing responses to sensory or motor stimuli vary dramatically across different precerebellar nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Several mechanistic implementations that promote adequate vesicle availability at vestibular synapses have been observed in other fast-firing neurons in the cerebral cortex, hippocampus, cerebellum, and brainstem (Crowley et al, 2007; Hallermann and Silver, 2013; Hu et al, 2014). Rapid repolarization of presynaptic action potentials by Kv3 currents (Gittis et al, 2010; Kolkman et al, 2011; Rudy and McBain, 2001) minimizes Ca2+ influx and reduces P R (Geiger and Jonas, 2000; Ritzau-Jost et al, 2014; Sabatini and Regehr, 1997; Taschenberger and von Gersdorff, 2000; Telgkamp et al, 2004). Large vesicle pools, multiple release sites, and rapid kinetics of vesicle translocation, docking, and priming maintain vesicle availability during high-rate transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanistic implementations that promote adequate vesicle availability at vestibular synapses have been observed in other fast-firing neurons in the cerebral cortex, hippocampus, cerebellum, and brainstem (Crowley et al, 2007; Hallermann and Silver, 2013; Hu et al, 2014). Rapid repolarization of presynaptic action potentials by Kv3 currents (Gittis et al, 2010; Kolkman et al, 2011; Rudy and McBain, 2001) minimizes Ca2+ influx and reduces P R (Geiger and Jonas, 2000; Ritzau-Jost et al, 2014; Sabatini and Regehr, 1997; Taschenberger and von Gersdorff, 2000; Telgkamp et al, 2004). Large vesicle pools, multiple release sites, and rapid kinetics of vesicle translocation, docking, and priming maintain vesicle availability during high-rate transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Since mossy fibres are heterogeneous and may differ physiologically (Kolkman et al . ; Chabrol et al . ), the stimulation electrode was positioned as consistently as possible to maximize replicability and reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Although initial in vitro recordings classified MVN neurons into 2 types on the basis of action potential waveforms (Serafin et al, 1991; Johnston et al, 1994), subsequent studies demonstrated that intrinsic physiological properties are distributed continuously rather than bimodally (du Lac and Lisberger 1995; Bagnall et al 2007). Many studies have now demonstrated specific differences in intrinsic excitability across MVN neurons with different axonal projections (Sekirnjak et al, 2006; Kolkman et al, 2011a and 2011b) and/or transmitter expression (Takazawa et al, 2004; Bagnall et al, 2007; Shin et al, 2011). The observation that Purkinje cells differentially innervate the somata and dendrites of several types of MVN neurons (Sekirnjak et al, 2003; Shin et al, 2011) complicates analyses of cerebellar learning.…”
Section: Introductionmentioning
confidence: 99%